Mesoporous silica coated Gd2(CO3)3:Eu hollow nanospheres for simultaneous cell imaging and drug delivery. Issue 67 (29th June 2016) - Wu, Yanli; Xu, Xianzhu; Chen, Xi; Yang, Ruchun; Xiao, Qiang; Li, Yongxiu
Abstract : The efficient optical/MR imaging capabilities, and the hollow structure make Gd2 (CO3 )3 :Eu@mSiO2 a promising platform for simultaneous bioimaging and drug delivery. Abstract : In the present work, mesoporous silica coated Gd2 (CO3 )3 :Eu hollow nanospheres (Gd2 (CO3 )3 :Eu@mSiO2 HNSs) were successfully synthesized via a facial route and characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), scanning electron microscope (SEM) infrared spectrometer (IR), energy dispersive X-ray spectrum (EDS) and Brunauer–Emmet–Teller (BET) surface area analysis. The results indicate that the prepared monodispersed nanoparticles are hollow spheres with a 400 nm sphere core and 30 nm thick shell and have a narrow size distribution. In vitro cell imaging of the hollow nanosphere shows Gd2 (CO3 )3 :Eu@mSiO2 HNSs were able to enter NCI-H460 lung cancer cells rapidly. The possibility of using the synthesized hollow nanospheres for magnetic resonance imaging was also demonstrated, and the hollow nanosphere displays a clear T 1 -weighted effect and could potentially serve as a bimodal T 1 -positive contrast agent. The drug loading and controlled release performance of Gd2 (CO3 )3 :Eu@mSiO2 HNSs was evaluated with doxorubicin hydrochloride (DOX) as a model drug at different pH values (pH = 7.4, 5.8). The Gd2 (CO3 )3 :Eu@mSiO2 HNSs showed sustainable pH dependent drug release property. Furthermore, the in vitro cytotoxic effect against NCI-H460 lung cancer cells of the DOX-loaded carriers was investigated in detail. In all, the Gd2 (CO3 )3 :Eu@mSiO2 HNSs as a new type of theragnostic (imaging and treatment) agent can provide new opportunities in cancer treatment.